Immediate adverse events following COVID-19 immunization. A cross-sectional study of 314,664 Italian subjects.: Immediate adverse events following COVID-19 immunization - Gianfredi, Vincenza; Minerva, Massimo; Casu, Giulia; Capraro, Michele; Chiecca, Greta; Gaetti, Giovanni; Mantecca Mazzocchi, Rosaria; Musarò, Patrizia; Berardinelli, Pasquale; Basteri, Paola; Bertini, Beatrice; Ferri, Camilla; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: The urgency of having rapidly safe and efficient COVID-19 vaccines called for the need to shorten trial phases, reduce sample sizes, and speed-up the approval process by the regulatory Agencies. In light of this, monitoring adverse effects (AEFI) (both immediate and at medium-long term) become of great importance. Aim of this cross-sectional study was to explore the associations between several factors and risk of immediate AEFI.Methods: Data come from the electronic dataset developed ad hoc to record demographic data, anamnesis and data related to immunization, set-up in the mass vaccination site in Novegro (Milan). Novegro mass vaccination site was one of the mass vaccinations sites with the highest flow in Lombardy Region, with a maximum capacity of 5,000 vaccinations/day. The center opened in April 2021 and closed the 1st of August 2021. A multivariable logistic regression model was used. Odds ratios adjusted (aOR) for age and sex are presented. Statistical significance was set at p